FROM COLONIZATION TO COMMUNICATION: MEDIA, NATIONALISM, AND MUSLIM STATES IN TRANSITION - Shafizan Mohamed (Journal of Islamic, Social, Economics and Development, 2023)
This article explores the interplay between post-colonial nationalist media and the socio-political landscapes of Muslim states in the regions of the Middle East, North Africa, and South Asia. In the aftermath of colonial rule, these regions witnessed the emergence of diverse media platforms that played pivotal roles in shaping national and religious identities, narratives, and aspirations. Drawing from post-colonial studies and media theory, this study examines the evolution, challenges, and impact of these media outlets.The article navigates a terrain marked by the echoes of colonialism, Islamic identities and nationhood through case studies that illuminate the nuances and commonalities that characterize the post-colonial nationalist media landscape in these Muslim states. The study underscores the significance of media as both agents and reflections of evolving post-colonial narratives, demonstrating their far-reaching consequences on socio-political dynamics in these regions. As these regions continue to grapple with the legacy of colonialism and navigate contemporary challenges, understanding the role of post-colonial nationalist media becomes increasingly essential. This study contributes to the broader discourse on media studies, post-colonialism, and nationalism, offering valuable insights into the multifaceted relationship between media and identity in Muslim societies.